Gig Economy in China? A Scoping Review - Xiao, Weihong; Liu, Yigang (Journal of Theory and Practice of Engineering Science, 2023)
This paper presents a comprehensive scoping review of the gig economy in China, shedding light on the multi‐dimensional experiences and challenges faced by gig workers. The review encompasses key themes such as work experience and well‐being, algorithmic management, labor control, worker solidarity, labor protection, policy development, and gender disparities. It uncovers that Chinese gig workers are often subjected to job insecurity, income instability, and variable working conditions. Furthermore, it reveals how algorithmic management and labor control can influence worker solidarity and labor activism, while highlighting the importance of clearly defined employment statuses and legal protection. Notably, the paper identifies gender disparities as a significant concern within the gig economy, requiring further intervention. Future research directions are also suggested, focusing on the ever‐ evolving gig work landscape and the effectiveness of proposed interventions and policy responses.